QUALITY ANALYSIS OF "KOSMOS" TKKS COMPOSE USING SELULOTIC MICROORGANISM - Angga Pramana; Anthony Hamzah; Ahmad Haitami; Deno Okalia (AGROINTEK, 2021)
This study aimed to determine the comparison of the chemical composition of oil oil palm empty friut bunches (TKKS) compost using cellulolytic microorganisms and TKKS compost. This research is a descriptive study that describes the chemical composition of compost with cellulolytic microorganisms. The treatments used in this study were the differences in the ratio of TKKS and cow dung KM1 (100: 0), KM2 (90:10), KM3 (80:20), KM4 (70:30), KM5 (60:40) and KM6 ( 50:50). This study's results were the selected treatment, namely KM5 with an N content of 0.73%, C-Organic 9.28%, C / N ratio 12.29%, P 0.42%, K 3.99%, while the TKKS content only. N 6.28%, C-Organic 14.19%, C / N ratio 2.26%, P 1.88%, K 2.51% and Mg 1.61%.